Il pensiero violento. Alcuni spunti di analisi degli anni Settanta - Scuto, Giuseppe (Il sogno della farfalla, 2008)
The article is a contribution to the current debate on the theoretical origins of violence in the history of italian extreme left of the 70s starting with an examination of the relationship between the theorization of one of the principle militant intellectuals of those years, Toni Negri, and the progressive development of the level of nihilistic violence expressed by the movement of his public manifestations. The analysis proposes a precise relationship between the writings of this author – who was not only an extra-parliamentary left-wing leader and a suspect driving force of terrorism but is currently a philosophy professor – and the influence of existentialist thinking which takes off from Heidegger and develops through the post-existentialists and Foucault. The problematic of the subject of class is examined in so far as it leaves the classic tenets of Marxism-Leninism and reaches a nihilistic existentialism, whose matrix, it is suggested, is a Nazi-type of thought.